Determinan Konservatisme Akuntansi pada Perusahaan Terindeks LQ45 - Apriana, Dina; Risal, Risal; Sartono, Sartono; Widyastuti, Reni Dwi; Wulandari, Renny (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2025)
This study aims to explore how independent commissioners, leverage, audit committee meeting frequency, financial distress, and firm size influence accounting conservatism. The research population consists of companies listed in the LQ45 index, with a sample of 23 firms selected through purposive sampling. The data were processed and analyzed using multiple linear regression techniques. The findings reveal that, on a partial basis, independent commissioners have a significant negative impact on accounting conservatism, while firm size shows a significant positive effect. In contrast, leverage, the frequency of audit committee meetings, and financial distress do not have a statistically significant influence on the level of accounting conservatism.